Methods Of Interactive Educational Methodology In Teaching A Foreign Language - Yulduz Abdullayevna Djurayeva (Euro Asian Journal Publishing, 2024)
The article talks about the skills of using interactive educational methods in teaching a foreign language
Keywords: Competence; professional competence; modern specialist; Insert method